Antimicrobial-resistant pathogens on the plate: A semi-quantitative hygiene risk evaluation of raw beef consumption in Ethiopia within a One Health context - Daniel Teshome Gebeyehu; Temechew Munaw Abebe; Ayalew Negash Shiferaw; Md Shahidul Islam; Gashaw Enbiyale Kasse (PLoS ONE, 2026)
Background While meat is a valuable source of nutrition, it can also serve as a vehicle for infectious and non-infectious diseases—especially when consumed raw. This risk becomes more serious when the meat harbors antimicrobial-resistant bacteria, often referred to as superbugs. This study assessed the health risks faced by consumers of raw beef in relation to infections from common enteric superbugs commonly transmitted through meat. Methods The investigation focused on detecting the prevalence of three key meat-borne bacteria— Salmonella , Shigella , and Escherichia coli —and evaluating their resistance to commonly used antibiotics. Bacterial identification was performed using culture techniques and biochemical tests, while antibiotic susceptibility was assessed via the disc diffusion method. The study also examined food safety practices at restaurants that serve raw beef, including hygiene measures and whether the meat underwent any thermal treatment. Health risk estimation was based on both likelihood factors (bacterial contamination and hygiene practices) and consequence factors (resistance to antibiotic treatments). Results Meat samples showed an overall bacterial contamination rate of 45.2%, with E. coli being the most prevalent (62.8%), followed by Shigella (32.7%) and Salmonella (4.4%). Alarmingly, 26.8% of the E. coli isolates were identified as the highly pathogenic E. coli O157:H7 strain. None of the restaurants applied any form of heat treatment (cooking or chilling) to the raw beef before serving, and 76% had poor hygiene practices based on bacterial contamination findings. All isolates were fully resistant to amoxicillin, and Salmonella strains also showed complete resistance to erythromycin. However, all bacteria remained 100% sensitive to chloramphenicol. Most isolates demonstrated multidrug resistance to commonly used antibiotics including ciprofloxacin, doxycycline, erythromycin, and streptomycin. The estimated health risk to raw beef consumers was high, primarily due to significant exposure levels and limited effectiveness of post-exposure treatment options. Conclusion The combined effects of high bacterial contamination, poor hygiene, lack of heat treatment, and widespread antibiotic resistance pose a potential hygiene-associated risk to raw beef consumers. Reducing this risk requires prompt action, including raising public awareness, enforcing strict meat hygiene standards, and implementing strategies to curb antimicrobial resistance.